TINJAUAN PERSPEKTIF SYARIAH TERHADAP PENGGUNAAN PINJAMAN ONLINE DI DESA PURWABAKTI, DESA CIASMARA DAN DESA CIASIHAN KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Rudianto, Derika; Thantawi, Tubagus Rifqy; Putra, Bayu Purnama (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The aim of this research is to determine an overview of the sharia perspective on the use of online loans in Purwabakti Village, Ciasmara Village and Ciasihan Village, Pamijahan District, Bogor. The research method used is a quantitative method. Respondents with the object studied and the sample results obtained were 300 respondents. The sharia perspective in this case is represented by the variable Understanding Compliance with Islamic Sharia (X1), and the variable Compliance with the Prohibition of Usury and Loan Interest (X2). Both were studied to review the variable Use of Online Loans (Y). The results of this research state that the variable Understanding Compliance with Islamic Sharia (X1) has a significant effect on the Use of Online Loans (Y). Likewise, the variables Compliance with the Prohibition of Usury and Loan Interest (X2) have a significant effect on the Use of Online Loans (Y). However, the significant influence of the variable Understanding Compliance with Islamic Sharia (X1) and the significant influence of the variable Compliance with the Prohibition of Usury and Loan Interest (X2), on the Use of Online Loans (Y) is a positive influence. The results of research in Purwabakti Village, Ciasmara Village and Ciasihan Village, Pamijahan District, Bogor, can be a meaningful lesson to reduce the use of online loans which cause many problems in society.